2013
DOI: 10.1371/journal.pone.0067021
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Adaptation Compensates Inactivation of Intestinal Arginine Biosynthesis in Suckling Mice

Abstract: Suckling mammals, including mice, differ from adults in the abundant expression of enzymes that synthesize arginine from citrulline in their enterocytes. To investigate the importance of the small-intestinal arginine synthesis for whole-body arginine production in suckling mice, we floxed exon 13 of the argininosuccinate synthetase (Ass) gene, which codes for a key enzyme in arginine biosynthesis, and specifically and completely ablated Ass in enterocytes by crossing Ass fl and Villin-Cre mice. Unexpectedly, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…Strains were originally obtained from The Jackson Laboratory: C57BL/6J, 000664; B6.129S7-Asl tm1Brle /J, 018830; B6.129P2-Lyz2 tm1(cre)Ifo /J, 004781; C57BL/6J-Tg(Itgax-cre,-EGFP) 4097Ach/J, 007567; B6.Cg-Tg(Tek-cre)1Ywa/J, 008863). Ass1 flox/flox ;Tie2-cre mice were a gift from S. E. Kohler (22). Mice for M. tuberculosis infections were transferred to the Laboratory Animal Medical Services biosafety level 3 facility at the University of Cincinnati 1 wk prior to inoculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains were originally obtained from The Jackson Laboratory: C57BL/6J, 000664; B6.129S7-Asl tm1Brle /J, 018830; B6.129P2-Lyz2 tm1(cre)Ifo /J, 004781; C57BL/6J-Tg(Itgax-cre,-EGFP) 4097Ach/J, 007567; B6.Cg-Tg(Tek-cre)1Ywa/J, 008863). Ass1 flox/flox ;Tie2-cre mice were a gift from S. E. Kohler (22). Mice for M. tuberculosis infections were transferred to the Laboratory Animal Medical Services biosafety level 3 facility at the University of Cincinnati 1 wk prior to inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…3D). To exclude a possible role for L-argininosuccinate, the intermediate of L-ARG synthesis from L-CIT, in inhibiting immune function, we crossed Ass1 flox/flox (22) with Tie2-and Lyz2-cre-expressing mice. M. bovis BCG-infected Ass1 flox/flox ;Tie2-cre, and Ass1 flox/flox ; Lyz2 cre/cre mice displayed an increase in mycobacterial load in the lung and spleen as compared with controls ( Supplemental Fig.…”
Section: Myeloid L-arg Synthesis Enhances Host Defense Against Mycobamentioning
confidence: 99%
“…Endothelial Ass- deficient ( Ass fl/fl /Tie2Cre tg/− ) mice were generated by crossing animals carrying the floxed allele Ass fl/fl [23] with Tie2Cre mice. The endothelial knockout animals will be designated as Ass-KO Tie2 , and the Ass fl/fl mice as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The endothelial knockout animals will be designated as Ass-KO Tie2 , and the Ass fl/fl mice as controls. We have previously shown that Ass fl/fl mice are indistinguishable from their wild type littermates [23]. 12- and 34-week-old male and female mice were used for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Got1은 amino acid metabolism에 중요한 효소로서 aspartate 에서 glutamate에게 α-amino group의 reversible transfer를 촉매한다 [14]. 많이 존재하고 있는 조직으로는 liver, heart, skeletal muscle, kidneys, brain, red blood cells이며 liver…”
unclassified